2020
DOI: 10.1108/ijhcqa-09-2019-0158
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional, multitiered daily rounding management in a high-acuity hospital

Abstract: PurposeThe purpose of this explanatory case study is to explain the implementation of interprofessional, multitiered lean daily management (LDM) and to quantitatively report its impact on hospital safety.Design/methodology/approachThis case study explained the framework for LDM implementation and changes in quality metrics associated with the interprofessional, multitiered LDM, implemented at Saint Francis Hospital and Medical Center (SFHMC) at the end of 2018. Concepts from lean, Total Quality Management (TQM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Teamwork in healthcare consists of information sharing, quality programme meetings, employee recognition and results sharing. In addition, empowerment plays a critical role in deploying improvement initiatives, which are in turn associated with job satisfaction, productivity, effectiveness and a lower propensity to leave [2,42,56].…”
Section: Critical Success Factors (Csfs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Teamwork in healthcare consists of information sharing, quality programme meetings, employee recognition and results sharing. In addition, empowerment plays a critical role in deploying improvement initiatives, which are in turn associated with job satisfaction, productivity, effectiveness and a lower propensity to leave [2,42,56].…”
Section: Critical Success Factors (Csfs)mentioning
confidence: 99%
“…The unique CSFs of LSS in healthcare compared to the manufacturing and service sector are the involvement and commitment of physicians [40,56], workload management and cross-functional collaboration [2,5]. It is reported that the involvement of physicians is critical, as improvement projects directly impact patient care and related treatments.…”
Section: Critical Success Factors (Csfs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Before implementing this initiative, unit-based rounding focused on clinical units and occurred on a weekly rotating basis. Over time, SFHMC adopted an LDM strategy whereby senior hospital leaders—including the president, chief nursing officer (CNO), chief medical officer, chief operating officer, chief quality officer, clinical department physician chairs, nursing directors—rounded every day by rotating through all hospital units, clinical and nonclinical, and worked with directors and managers to achieve and maintain their unit-based targets 21. This gave senior leadership an opportunity to discuss the care SFHMC patients were receiving and interact with staff to foster an environment centralized around patient safety and experience.…”
Section: Methodsmentioning
confidence: 99%
“…Over time, SFHMC adopted an LDM strategy whereby senior hospital leaders-including the president, chief nursing officer (CNO), chief medical officer, chief operating officer, chief quality officer, clinical department physician chairs, nursing directors-rounded every day by rotating through all hospital units, clinical and nonclinical, and worked with directors and managers to achieve and maintain their unit-based targets. 21 This gave senior leadership an opportunity to discuss the care SFHMC patients were receiving and interact with staff to foster an environment centralized around patient safety and experience. The senior leaders also mandated that their work schedule set aside dedicated appointments to engage with patients, verifying firsthand that their care was managed appropriately.…”
Section: Unit-based Nursing and Executive Leadership Roundingmentioning
confidence: 99%